GENETIC ASPECTS OF INDIRECT HYPERBILIRUBINAEMIA IN NEWBORNS - Katja Jarc Georgiev; Manca Velkavrh (The Society for Children with Metabolic Disorders, 2022)
Indirect hyperbilirubinaemia is a common finding in the neonatal period. There are numerous causes of neonatal indirect hyperbilirubinemia, from excessive bilirubin production, impaired hepatic bilirubin uptake or bilirubin conjugation and increased enterohepatic circulation. Genetic testing is increasingly used when investigations do not determine the cause of unconjugated hyperbilirubinaemia. The genetic basis of indirect hyperbilirubinaemia is broad and encompasses a large number of genes. The most commonly encountered and researched are haemolytic causes of hyperbilirubinaemia and disorders of bilirubin conjugation. Recently, however, there is growing evidence of gene polymorphism as a cause of unconjugated hyperbilirubinaemia in the neonatal period.